Determinantes da Transferência de Tecnologia na Agroindústria Brasileira de Alimentos: Identificação e Caracterização - Cribb, André Yves (Journal of Technology Management & Innovation, 2009)
This article aims to identify and characterize determinants of technology transfer, from the perspective of agro-industrial firms operating in Brazil, and under the light of the core theoretical concepts. By reaching this objective, the article provides a basis for studies and practices relating to technological change in the agrifood sector. Particularly, it may help in defining or reformulating public policies favorable for the generation and application of technologies in the Brazilian food industry.